1974
DOI: 10.1155/tsm.1.233
|View full text |Cite
|
Sign up to set email alerts
|

Texture of Metals

Abstract: A condensed review of casting, deformation, and annealing textures of polycrystalline metals and alloys is presented. It is intended to provide an informative but simplified reference for researchers, engineers, and students who are seeking quick information on the development of textures in various metal objects, and for those who are primarily interested in the textures of non-metallic materials, but wish to acquire a general background knowledge on the texture formation in metals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
49
1

Year Published

1976
1976
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(62 citation statements)
references
References 0 publications
12
49
1
Order By: Relevance
“…Some spread from the <110> texture towards <113> is also seen in Fig.3. This texture is similar to those obtained after heavy compression of pure fcc metals with medium and high SFE values [14,15].…”
supporting
confidence: 84%
“…Some spread from the <110> texture towards <113> is also seen in Fig.3. This texture is similar to those obtained after heavy compression of pure fcc metals with medium and high SFE values [14,15].…”
supporting
confidence: 84%
“…5 both (a) without and (b,c) with dynamic testing. Thus, the alloy has a random texture after solution treatment but it develops a deformation texture after dynamic testing at (b) 298 and (c) 673 K. This texture is typical of fcc metals with high stacking fault energies after compression testing and it is characterized by a fibre-type texture where the compression axis is the fibre axis [69,70]. As is evident from Figs.…”
Section: Grain Structure and Texture Of The Coarse-grained Al-mg-sc Amentioning
confidence: 88%
“…For body-centered cubic (bcc) iron-based systems, the deformation texture after compression is dominated by h100i and h111i fiber texture components aligned with the compression axis (CA), and it is generally found that the h100i component weakens during recrystallization, whereas the h111i fiber texture strengthens significantly. [1][2][3][4] In a previous study [3] on a modified ferritic/martensitic 9Cr-1Mo steel where samples were deformed to a strain of 0.5 either by quasistatic compression (QSC) or by dynamic plastic deformation (DPD), [5,6] it has been found that DPD resulted in a stronger h111i + h100i fiber texture and in faster recrystallization than QSC. The faster recrystallization was attributed to a finer boundary spacing and, therefore, a higher energy stored during DPD as compared to QSC.…”
Section: Introductionmentioning
confidence: 99%